Emergence and Genesis of Tonality in Chadic: A Contribution to the Linguistic History of Northeast Africa - Jungraithmayr, Herrmann (Folia Orientalia, 2024)
The Chadic languages, numbering approximately 150 and spoken in central Sudan, did not—as members of the Afroasiatic phylum—originally dispose and make use of the structural feature of tonality. The article describes the gradual emergence of tonality as a phonemic means and change from a predominantly segmental stage in the east (Eastern Chad) to a suprasegmental (tonal) type of structure in the west (Northern Nigeria); the five-tone-level language of Mushere on the central Nigerian Plateau represents the peak of this transformational process from segmentality to tonality. In order to illustrate the purely tonal structure of this highly emancipated Afroasiatic language a version of the Lord’s Prayer is added, translated for the first time into Mushere by Philibus Diyakal.